Secret seven win through - Blyton, Enid. (b, 2004)
The Seven are evicted from their shed while it is painted, and find a glorious new meeting place? A cave! But when there is a strange intruder, a mystery begins? Who is Albert Tanner, and what is the excitement surrounding the scarecrow?
Keywords: Adventure stories; English fiction -- Children's stories